Risk Assessment and Detection of Legionella species in the Water System of A Luxury Hotel in Dhaka city, Bangladesh - Naher, Nazmun; Bari, Md Latiful; Ahmed, Sangita (Bangladesh Journal of Microbiology, 2024)
Legionella cause Legionnaires’ disease and Pontiac fever, and, more rarely, extrapulmonary infections, collectively referred to as legionellosis. Legionella pneumophila causes serious pneumonic infections, and water and Air Conditioning systems are a common source. We performed this study focusing on identifying and assessing the potential sources of Legionella spp. in a luxury hotel water system in Dhaka, Bangladesh. As hotels often have complex water distribution systems that can harbor and facilitate the growth of these bacteria, understanding the risks and implementing effective control measures is crucial for public health. This study determines the presence of Legionella spp. and potential factors contributing to their proliferation within the hotel water systems. In total 42 water samples and six swabs from 7 different points were collected multiple times between March 2018 and April 2019 and were analyzed. Legionella spp. was detected in all samples (100%) tested. The highest colony counts were observed in water samples from the hot water tank and cooling system. The findings highlight the importance of regular monitoring, maintenance, disinfection, and flushing protocols to mitigate the risk of Legionella spp., contamination, and subsequent health issues among hotel guests and staff. Bangladesh J Microbiol, Volume 40, Number 1, June 2023, pp 33-39